Epidemiology and Genomic Characteristics of Bloodstream Infection Caused by Carbapenem-Resistant Klebsiella pneumoniae With Decreased Susceptibility to Aztreonam/Avibactam in China - Yu, Wei; Shen, Ping; Chen, Yunbo; Zhou, Kai; Chi, Xiaohui; Xiao, Yonghong (Frontiers in Cellular and Infection Microbiology, 2022)
Aztreonam/avibactam (AZA), as one of novel β-lactamases and β-lactamase inhibitor combinations, is considered to be a promising option for bloodstream infection (BSI) carbapenem-resistant Klebsiella pneumoniae (CR-Kp). However, decreased susceptibility of AZA activity in Enterobacterales has been reported. The aim of this study was to identify the mechanisms of BSI CR-Kp with decreased susceptibility of AZA (minimal inhibitory concentration above 16/4 mg/L) (AZAH-Kp). Nine BSI AZAH-Kp isolates were screened from 317 CR-Kp isolates in Blood Bacterial Resistant Investigation Collaborative System (BRICS) program. Whole genome sequencing, bioinformatics analysis, and the relative expression of blaKPC, ompK35 and ompK37 were explored for CR-Kp with decreased susceptibility to AZA. The results revealed elevated inhibitory concentration of AZA has emerged in CR-Kp before previous clinical exposure. In addition, decreased AZA susceptibility was associated with higher KPC expression and changes of OmpK35-37.